2009
DOI: 10.1097/htr.0b013e3181a40590
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Psychiatric Symptoms Following Preschool Childhood Mild Traumatic Brain Injury

Abstract: Preschool MTBI is associated with persistent negative effects on psychosocial development. These continuing problems are consistent with the view that preschool years represent a period of particular vulnerability following MTBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
114
3
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(119 citation statements)
references
References 44 publications
1
114
3
1
Order By: Relevance
“…However, two recent longitudinal investigations conducted in New Zealand and Germany, respectively, concluded that TBI is not likely to cause neurocognitive impairment in children and adolescent (18,19). The discrepancy between our study and these two investigations may be explained by differences in study designs and the environmental characteristics of the target populations.…”
Section: Articlescontrasting
confidence: 54%
See 1 more Smart Citation
“…However, two recent longitudinal investigations conducted in New Zealand and Germany, respectively, concluded that TBI is not likely to cause neurocognitive impairment in children and adolescent (18,19). The discrepancy between our study and these two investigations may be explained by differences in study designs and the environmental characteristics of the target populations.…”
Section: Articlescontrasting
confidence: 54%
“…In addition, several studies have suggested that children with moderate to severe TBI are significantly more likely to develop ADHD symptoms than are those with mild TBI (8,(13)(14)(15)(16)(17). A longitudinal birth cohort study reported no association between preschool mild TBI and ADHD after adjusting for potential covariates (18). Nevertheless, a prospective cohort study reported that children with mild TBI have a higher risk of hyperactivity in the first year after injury (19).…”
mentioning
confidence: 90%
“…A similar line of research which explores a potentially indirect mechanism in the relationship between TBI and crime focuses on mental illness following brain injury. These studies suggest that those with TBI, including both adolescents and adults, are more likely to have symptoms of a psychiatric disorder (e.g., ADHD, bipolar disorder, major depression, panic disorder, depression) as well as increased aggressive behaviors at follow-up (Bloom et al, 2001;Cole et al, 2008;Dinn, Gansler, Moczynski, & Fulwiler, 2009;Gerring et al, 2009;Hesdorffer, Rauch, & Tamminga, 2009;Koponen, 2005;Max, Castillo, Lindgren, & Arndt, 1998;Max, Robertson, & Lansing, 2001;McKinlay, Grace, Horwood, Fergusson, & MacFarlane, 2009;VanReekum, Bolago, Finlayson, Garner, & Links, 1996). Thus, having TBI might also result in symptoms of mental illness, substance abuse, or violence which could exacerbate the likelihood of arrest.…”
Section: Traumatic Brain Injury and Criminal Behaviormentioning
confidence: 99%
“…Specifically, animal models of repeated pmTBI indicate increased memory impairment, astrocytic reactivity, and axonal injury relative to a single injury model (Prins et al, 2010). Preliminary evidence of increased deficits after a quick return to play after pmTBI also exists in human injury models as well (McCrory et al, 2009;Guskiewicz and Valovich McLeod, 2011;Lincoln et al, 2011). The current definition of mTBI is variable (Ruff et al, 2009;Rosenbaum and Lipton, 2012) and primarily determined by clinical observations and selfreported symptomatology rather than objective criteria.…”
Section: Figurementioning
confidence: 99%
“…In summary, pmTBI is associated with an increased incidence of neuropsychiatric conditions (McKinlay et al, 2009), delays in academic achievement, and decrease in overall quality of health (Yeates et al, 2012). Understanding the neuropathological underpinnings of these deficits is critical for both diagnostic considerations and developing novel treatment strategies.…”
Section: Figurementioning
confidence: 99%